PENGARUH PEMBERDAYAAN DAN KINERJA UMKM TERHADAP KESEJAHTERAAN ANGGOTA UMKM PADA KOMUNITAS JAWARA DI KECAMATAN SUKMAJAYA - Ramadhanti, Suci; Mariah, Mariah (Journal of Development Economics and Digitalization, Tourism Economics, 2024)
This research aims to determine the influence of empowerment and performance of MSMEs on the welfare of MSME members in the Jawara Community in Sukmajaya District. This research uses descriptive quantitative methods. Data was obtained by distributing questionnaires using a Likert scale. The population in this study was members of the Jawara community in Sukmajaya District, totaling 642 people with a total sample of 87 respondents. The criteria for respondents were MSME actors who were members of the Jawara community, Sukmajaya subdistrict, Depok city and this research was analyzed using IBM SPSS version 20 software. Samples were taken using the probability sampling method. The results of research on the T test show that empowerment partially (alone) has an effect on welfare. Performance partially (separately) influences the welfare of MSMEs. Empowerment (X1) and Performance (X2) simultaneously influence Welfare (Y). This is an open access article under the CC–BY-SA license.